POLITICAL HIERARCHIES IN PHARMACEUTICAL SALES: TERRITORY TRANSFERS, KPI GOVERNANCE, AND RESIGNATION DECISIONS AMONG MEDICAL REPRESENTATIVES IN INDONESIA - Eman Sulaiman (PATEMON: Multidisciplinary Research, 2025)
Purpose: This qualitative, theory-building study develops an evidence-informed framework to explain why pharmaceutical medical representatives (MRs) in Indonesia may resign after being reassigned to distant or low-potential territories following perceived “like–dislike” supervisory dynamics. Research Methodology: We propose an embedded qualitative case study design in an Indonesian pharmaceutical company, integrating salesforce governance (territory design, KPI setting, and incentive rules) with organizational behavior theories on perceived organizational politics, leader member exchange (LMX) differentiation, organizational justice, and job demand resources. Results: The framework specifies three mechanism chains. First, supervisory favoritism fosters LMX differentiation, which in turn heightens employees’ perceptions of organizational politics and justice violations. Second, opaque governance of KPI and incentive systems undermines procedural justice, thereby weakening psychological safety. Third, when territory reassignment is interpreted as an informal sanction, it escalates job demands and subsequently increases withdrawal behaviors and turnover intentions, including resignation. Based on these mechanisms, we develop a set of research propositions and provide a field ready interview protocol for MR–supervisor dyads and, where relevant, Sales Operations and HR stakeholders. Limitations: As a conceptual qualitative study, empirical validation through in-depth interviews and document analysis is required. Contribution: The study connects political dynamics in pharmaceutical sales management to territory governance and KPI incentive systems, offering a practical agenda to reduce preventable turnover while maintaining ethical promotion standards (e.g., IPMG Code of Ethics).